Service-Learning: Analysis of the first workshop to introduce this methodology in a private university in Nicaragua - Pereira-Martín, Tamara; Leal Saballos, Carlos; Castillo Gurdián, Erick; Guerrero-Guillén, Roxana (Scientific journal of social studies, 2023)
In line with its vision and mission, a private university in Nicaragua is promoting the use of the active methodology known as Service-Learning (ApS) so that students develop the skills and competencies necessary for their future work performance and clarify their vocational individual interests. A pilot project was implemented as a first training experience so that part of the teaching staff could use ApS in their classes and as a first step for its future implementation throughout the university. The objective of this study is to describe the perception of five participants of the pilot workshop that took place in June 2022 in order to identify possible improvements in future training on said methodology. It is about evaluating the effectiveness of the ApS workshop, identifying the successful practices and challenges experienced from the perspective of the authorities, the trainer and the trained teachers and knowing if the workshop was enough for teachers to apply this methodology in their classes. The mixed methodology is selected, with survey techniques, as well as semi-structured interviews. Although it is true that the results show a general good perception of those who participated regarding the correct organization of content and approach to the topic, limitations and points for improvement were found for future training.
Keywords: Service-Learning; university; ApS workshop